Ultrasound-guided percutaneous nephrolithotomy without fluoroscopy: early surgical experience with video-based technical insights - Tan, Chenghao; Li, Xin; Zhang, Xiaochun; Wang, Gang; Xiong, Gengyan (Frontiers in Surgery, 2025)
ObjectivesTo assess the feasibility, safety, and short-term outcomes of ultrasound-guided percutaneous nephrolithotomy (PCNL) performed by a single early-career urologist without fluoroscopic guidance.MethodsWe retrospectively analyzed 70 consecutive ultrasound-guided PCNL cases performed independently by a single early-career urologist at Peking University First Hospital. All procedures employed single-tract, rigid ureteroscopy-assisted access under real-time ultrasound guidance without fluoroscopy. Perioperative parameters included access success, operative time, hemoglobin drop, stone-free rate, and complications. An accompanying educational video was included to facilitate reproducibility.ResultsThe stone-free rate after a single procedure was 75.7%, rising to 88.6% at 6-month follow-up. No major complications occurred. The mean stone size was 2.22 cm. Mean access time was 9 min. Access was successfully achieved in all cases. These outcomes were achieved despite the surgeon's early learning curve, reflecting a high degree of technical feasibility and safety under structured mentorship.ConclusionsUltrasound-guided PCNL is a safe, effective, and radiation-free alternative to fluoroscopy-guided procedures. It can be reliably adopted early in surgical practice. The accompanying video supports broader understanding and dissemination of this radiation-free approach, especially in resource-limited or high-volume centers.